Science diplomacy in the European Union: mapping the Portuguese case (1986–2021) - Marta Abrantes; Raquel Vaz-Pinto (Humanities & Social Sciences Communications)
Abstract Science diplomacy has been assuming a growing importance in the actions of states due to their need to respond to global challenges and to strengthen their power and influence through competitive advantage based on science and technology. Within the European Union (EU), science diplomacy can be seen as an instrument for the integration of the European project and for the projection of EU influence, standards, and values in the relationship with third countries. In this context, the present work aims at understanding and characterizing Portugal’s science diplomacy model and its relationship with the European project from 1986 (the moment of Portugal’s accession to the European Economic Community) to 2021. To this end, we mapped the science diplomacy designed and implemented by the Portuguese State by identifying its different instruments based on a methodology suggested by the European Commission, Directorate-General for Research and Innovation and Van Langenhove in 2017 and using a timeframe suggested by Heitor in 2015. The obtained dataset was subjected to a combination of analytical frameworks, including the general framing analysis proposed by Ruffini and Krasnyak in 2023, which allowed us to identify the objectives, strategic drivers and implementation approach of the Portuguese science diplomacy model. In the period under study Portugal has been developing a science diplomacy in parallel with the European project without ever losing a global vision of the relations in the field of science and technology.